Vaccination hesitation in children under five years of age: a scoping review - Eugênio Barbosa de Melo Júnior; Priscilla Dantas Almeida; Beatriz Mourão Pereira; Paulo de Tarso Moura Borges; Elucir Gir; Telma Maria Evangelista de Araújo (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to synthesize scientific evidence on vaccine hesitancy in children under five years of age and its associated factors. Methods: a scoping review, conducted according to the methodological structure proposed by the JBI. Searches were carried out in the Latin American and Caribbean Center on Health Sciences Information, Scientific Electronic Library Online and PubMed databases, including gray literature. Studies in English, Spanish and Portuguese were included, without temporal delimitation. Editorials, studies that did not address vaccine hesitancy in children under five years of age and were not aligned with the objective and research question were excluded. The sample consisted of 18 articles. Results: misinformation, concern about adverse effects, distrust about efficacy, affliction regarding administration simultaneously, and insecurity in relation to the laboratories were the reported reasons. Conclusions: strategies are needed to combat the lack of information about immunobiological agents, as misinformation was the main factor in parents' vaccine hesitation.